The role of complex interactions between the intestinal flora and host in regulating intestinal homeostasis and inflammatory bowel disease - Li, Siyu; Xu, Kan; Cheng, Yi; Chen, Lu; Yi, Ailin; Xiao, Zhifeng; Zhao, Xuefei; Chen, Minjia; Tian, Yuting; Meng, Wei; Tang, Zongyuan; Zhou, Shuhong; et al. (Frontiers in Microbiology, 2023)
Pharmacological treatment of inflammatory bowel disease (IBD) is inefficient and diffi-cult to discontinue appropriately, and enterobacterial interactions are expected to provide a new target for the treatment of IBD. We collected recent studies on the enterobacterial inter-actions among the host, enterobacteria, and their metabolite products and discuss potential therapeutic options. Intestinal flora interactions in IBD are affected in the reduced bacterial diversity, impact the immune system and are influenced by multiple factors such as host genetics and diet. Enterobacterial metabolites such as SCFAs, bile acids, and tryptophan also play important roles in enterobacterial interactions, especially in the progression of IBD. Therapeutically, a wide range of sources of probiotics and prebiotics exhibit potential ther-apeutic benefit in IBD through enterobacterial interactions, and some have gained wide recognition as adjuvant drugs. Different dietary patterns and foods, especially functional foods, are novel therapeutic modalities that distinguish pro- and prebiotics from traditional medications. Combined studies with food science may significantly improve the therapeutic experience of patients with IBD. In this review, we provide a brief overview of the role of enterobacteria and their metabolites in enterobacterial interactions, discuss the advantages and disadvantages of the potential therapeutic options derived from such metabolites, and postulate directions for further research.